Simultaneous Measurement of the Refractive Index and Temperature Based on Microdisk Resonator With Two Whispering-Gallery Modes - Tao Ma; Jinhui Yuan; Lei Sun; Zhe Kang; Binbin Yan; Xinzhu Sang; Kuiru Wang; Qiang Wu; Heng Liu; Jinhui Gao; Chongxiu Yu (IEEE Photonics Journal)
In this paper, a microdisk resonator with two whispering-gallery modes (WGMs) is proposed for label-free biochemical sensing. According to the transmission responses of the two WGMs with different coupling gaps, there is the critical coupling status for the WGM (0, 36) while there is no critical coupling status for the WGM (1, 28). For the WGMs (0, 36) and (1, 28), the refractive index (RI) sensitivities of 45.8821 and 72.9402 nm/RIU are obtained, and the corresponding RI detection limits (DLs) of 8.5902 × 10−4 and 1.9228 × 10−3 RIU are achieved, respectively. Moreover, the proposed sensor also has the temperature sensitivities of 0.0730 and 0.0703 nm/K, which correspond to the temperature DLs of 0.1631 and 0.6263 K, respectively. By constructing a characteristic matrix, it is demonstrated that simultaneous measurement of the RI and temperature can be achieved.